Narrative Psychology and Vygotsky in Dialogue: Changing Subjects - Garraway, James (Critical Studies in Teaching and Learning, 2023)
In a special edition of the journal ‘Alternations’ (2019) on the extended programmes in universities in South Africa, authors highlighted the paucity of theoretical underpinnings in published articles on teaching approaches (these programmes are aimed at supporting non-traditional students’ ability to bridge between school and university). One of the concerns was that although there was much reference to Vygotsky’s work his developmental theories were largely underdeveloped. Jill Bradbury’s book Narrative Psychology and Vygotsky in Dialogue, though not primarily focused on new students’ learning, may offer readers greater insight into the use of Vygotsky’s principles in student learning. Jill Bradbury is a Professor of Psychology at the University of the Witwatersrand, South Africa. Her teaching and research focus is on narrative psychology with a particular focus on sociohistorical theories of personhood development, educational transformation and social change, and the role narrative may play in these. She is the principle investigator in the ‘Narrative Enquiry for Social Transformation’ (NEST) project.